2021
DOI: 10.48550/arxiv.2106.10963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wireless Communication Aided by Intelligent Reflecting Surface: Active or Passive?

Abstract: In this letter, we consider an intelligent reflecting surface (IRS)-aided wireless communication system, where an active or passive IRS is employed to assist the communication between an access point and a user. First, we consider the downlink/uplink communication separately and optimize the IRS placement for rate maximization with an active or passive IRS. We show that the active IRS should be deployed closer to the receiver with the IRS's decreasing amplification power; while in contrast, the passive IRS sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…And if the fading coefficient is large, the signals from this longer reflection link lose more power than that from the short direct link, resulting in a limited secrecy performance gain compared with the one without IRS. Recently, a new concept of active IRS has been proposed [20]- [24] which can combat this "double fading" effect. Compared with passive IRS, the active IRS directly reflects the incident signal with the power amplification in the electromagnetic (EM) level, and it still takes the advantage of IRS that no complex and powerhungry radio frequency (RF) chain components are needed.…”
Section: A Backround and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…And if the fading coefficient is large, the signals from this longer reflection link lose more power than that from the short direct link, resulting in a limited secrecy performance gain compared with the one without IRS. Recently, a new concept of active IRS has been proposed [20]- [24] which can combat this "double fading" effect. Compared with passive IRS, the active IRS directly reflects the incident signal with the power amplification in the electromagnetic (EM) level, and it still takes the advantage of IRS that no complex and powerhungry radio frequency (RF) chain components are needed.…”
Section: A Backround and Motivationmentioning
confidence: 99%
“…Therefore, the physical size of the active IRS can be reduced, making it more suitable for UAV communication limited by the payload. Furthermore, it offers more freedom to design secure beamforming by optimizing the amplitudes of the reflection coefficients instead of just phases, resulting in more flexibility to reconfigure the wireless propagation environment [24], [25]. As a result, the secure UAV communication enhanced by active IRSs is a promising solution for providing high-efficient communication services.…”
Section: A Backround and Motivationmentioning
confidence: 99%
“…Moreover, we observe from (2) that the noises at the IRS can be divided into two categories, i.e., dynamic noise and static noise [9]. In particular, the dynamic noise is generated due to the power amplification [11], where d ∈ C N T ×1 is modelled as additive white Gaussian noise (AWGN) with variance…”
Section: System Modelmentioning
confidence: 99%
“…To circumvent these issues, the authors of [9] recently proposed a new IRS structure, namely, active IRSs. In particular, equipped with reflection-type amplifiers [10], [11], active IRSs can not only reflect the incident signals by manipulating the programmable IRS elements, but also amplify the reflected signal with the support of an extra power supply. We note that active IRSs are fundamentally different from full-duplex amplify-and-forward (FD-AF) relays in terms of hardware architecture and the mode of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…While we have shown that the passive IRS is able to improve the WPT/SWIPT/WPCN performance at low energy and hardware cost, a large number of reflecting elements is practically required due to the product-distance path loss caused by IRS's passive reflection. To overcome this drawback, a new type of IRS, called active IRS, has been recently proposed [89], [90], as shown in Fig. 12(d).…”
Section: Active/transmissive Metasurface For Wpt/wiptmentioning
confidence: 99%